373 Historical Use of Substances for Insomnia Impacts Current Beliefs about Hypnotic Medications. (3rd May 2021) - Dietch, Jessica; Simpson, Norah; Tutek, Joshua; Tully, Isabelle; Rangel, Elizabeth; Manber, Rachel
Abstract: Introduction: The purpose of the current study was to examine the relationship between current beliefs about hypnotic medications and historical use of prescription hypnotic medications or non-prescription substances for sleep (i.e., over the counter [OTC] medications, alcohol, and cannabis). Methods: Participants were 142 middle age and older adults with insomnia (M age = 62.9 [SD = 8.1]; 71.1% female) enrolled in the RCT of the Effectiveness of Stepped-Care Sleep Therapy In General Practice (RESTING) study. Participants reported on history of substances they have tried for insomnia and completed the Beliefs about Medications Questionnaire-Specific with two subscales assessing beliefs about 1) the necessity for hypnotics, and 2) concerns about potential adverse consequences of hypnotics. Participants were grouped based on whether they had used no substances for sleep (No Subs, 11.6%), only prescription medications (Rx Only, 9.5%), only non-prescription substances (NonRx Only, 26.6%), or both prescription and non-prescription substances (Both, 52.3%). Results: Sixty-one percent of the sample had used prescription medication for sleep and 79% had used non-prescription substances (74% OTC medication, 23% alcohol, 34% cannabis). The greater number of historical substances endorsed, the stronger the beliefs about necessity of hypnotics, F(1, 140)=23.3, p<.001, but not about concerns. Substance groups differed significantly on necessity beliefs, F(3, 1)=10.68, p<.001; post-hocs revealed the Both group had stronger beliefs than the No and NonRx Only groups. Substance groups also differed significantly on the concerns subscale, F(3, 1)=6.68, p<.001; post-hocs revealed the NonRx Only group had stronger harm beliefs than the other three groups. Conclusion: The majority of the sample had used both prescription and non-prescription substances to treat insomnia. Historical use of substances for treating insomnia was associated with current beliefs about hypnotics. Individuals who had used both prescription and non-prescription substances for sleep in the past had stronger beliefs about needing hypnotics to sleep at present, which may reflect a pattern of multiple treatment failures. Individuals who had only tried non-prescription substances for sleep may have specifically sought alternative substances due to concerns about using hypnotics. Future research should seek to understand the impact of treatment history on engagement in and benefit from non-medication-based treatment for insomnia. Support (if any): 1R01AG057500; 2T32MH019938-26A1